Persistent Posttraumatic Wrist Pain - Tuberculosis Infection Should be in the Differential Diagnosis. A Rare Case Report - Soman, Shardul Madhav (J Orthop Case Reports, 2015)
INTRODUCTION: It is uncommon for hand surgeons to diagnose and treat persistent post-traumatic radius fracture on the lines of tuberculosis infection even in developing countries especially when the clinical picture resembles more of a complex regional pain syndrome (CRPS). Although it works for many patients, some conditions that affect the wrist don’t fall in this category and worsen with this treatment practice. We present a patient who had an extra articular distal radius fracture treated initially with percutaneous pinning and was treated as CRPS for the next ten months by local physician. He was eventually diagnosed with advanced tuberculosis of the wrist and a total wrist arthrodesis was performed. Only one such case was ever reported in literature. CASE REPORT: A 50-year-old male, came to our institute with the history of pain and fullness in the wrist since one year. One year ago he had developed an extra articular fracture of the distal radius which was initially treated with percutaneous pinning and a below elbow cast for six weeks. On removal of the cast one pin was found loose and the other removed eventually after two more weeks of immobilization. Patient continued to have pain with fullness around the wrist which was treated at local place with anti inflammatory agents and ice application. Patient had complaint of other constitutional symptoms. Initially patient had full range of motion which gradually decreased. X-ray showed characteristic signs suggesting of extensive tuberculosis of distal radius which was operated with wrist arthrodesis. Per operatively, fine rice granular granulation tissue was found, histopathological examination of which confirmed the diagnosis of tuberculosis. CONCLUSION: Though rare, every case of distal radius fracture complaining of chronic pain and signs suggestive of CRPS should have tuberculosis as one of the differential diagnosis, even if patient does not present any signs of tuberculosis or any primary focus is not identified. Even though skeletal tuberculosis per se is hematogenous in origin, inoculation from the pin site can be a cause and hence proper sterilization techniques should be used.